Transformasi Tradisi Nadran pada Masyarakat Nelayan di Pelabuhan Karangantu: Studi Deskriptif pada Masyarakat Nelayan Karangantu - Sakinah, Elsa; Jamaludin, Ujang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the history, implementation process and meaning and transformation of the nadran tradition culture in Karangantu Port. The research method used is a qualitative approach with a descriptive method. The location of the study was carried out in Karangantu Port, Banten Village, Kasemen District, Serang City, Banten Province. The sources determined in the study were religious figures, fishermen, and the community. In addition, the author used data collection through observation, interviews and documentation. The results of the study indicate that the process of implementing the nadran tradition in Karangantu Port is a series of activities that reflect gratitude, respect for the sea, and strengthen the social solidarity of the fishing community. From a cultural perspective, the main value reflected in this tradition is gratitude to God for the sea products given. Meanwhile, from a religious perspective, nadran reflects a form of gratitude to God for the abundance of sustenance from the sea. However, the nadran tradition in Karangantu Port has undergone quite significant changes due to the influence of internal and external factors of society. This has encouraged simplification in nadran. Despite the shift in form, the main value of nadran as a form of gratitude to God and an expression of social solidarity is maintained. Keywords: Tradition of Nadran, Fishermen, Karangantu.